Continuous in vitro propagation of the malaria parasite Plasmodium vivax - Golenda, Claudia F. (The National Academy of Sciences of the USA, 1997)
The difficulty in controlling Plasmodium vivax, the most common cause of human malaria, has been complicated by growing drug resistance. We have established a method to cycle parasite generations in continuous culture using human blood cells. Chesson strain parasites were passaged from owl monkey erythrocytes to human reticulocytes in McCoy’s 5A medium modified with L-glutamine with 25 mM Hepes buffer supplemented with 20% AB(+) human serum. Reticulocytes were separated by differential centrifugation in homologous plasma from the peripheral blood of a hemochromatosis patient. Parasites were grown during each 48-hr cycle in a static candle jar environment until the beginning of schizogony, at about 36–40 hr, when reticulocytes were added and cultures transferred to a shaker for 10–12 hr. The addition of a concentration of 10% reticulocytes resulted in stabilizing parasite densities between 0.28 and 0.57 after cycle 3 and increasing the total number of parasites at least 2-fold with each generational cycle. Cultured parasites successfully infected an owl monkey. The morphology of cultured parasites was typical of P. vivax, with highly ameboid trophozoites evident; however, infected erythrocytes were enlarged and distorted on thin film preparations. The species identity of cultivated parasites was confirmed by analysis of the A and C 18S rRNA genes from genomic DNA and expression of only the A gene during erythrocytic asexual growth. The ability to culture P. vivax opens new opportunities to develop vaccines, test drugs, and clone parasites for genome sequencing.